Development of E-Module for Electrolyte and Nonelectrolyte Solution Based on Problem Based Learning Integrated with STEAM for SMA/MA - Safitri, Dara Cyntia; Andromeda , Andromeda (FKIP - Universitas Riau, 2023)
Students have difficulty understanding electrolyte and nonelectrolyte solution materials, because they are required to understand three representations including symbolic, macroscopic, and submicroscopic. With e-module, it can increase students' interest in learning and e-module is designed so that students can study material independently and actively. This study aims to produce e-modules of electrolyte and nonelectrolyte solutions based on steam integrated problem-based learning for SMA / MA to analyze the validity and practicality of the e-module. This study is 4D development model. E-module validity test was carried out by 3 lecturers of FMIPA an FT UNP, and 2 chemistry teachers. Practicality test was carried out by 2 chemistry teachers and 30 students of class XI of SMAN 1 Payakumbuh. Validity questionnaires were analyzed using the Aikens'V formula and practicality questionnaires were analyzed using descriptive statistical percentages. From results of the study, average score of Aikens'V was obtained at 0.97 with a valid category. Practicality value of e-modules obtained is 98%, 96% respectively with practical category. Based on results, can be concluded e-module is valid and practical. Therefore, this research can be continued to stage of effectiveness testing, so that this e-module can be used in the learning process.